Advantageous Smallness in Contests - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2021)
A standard result in contests is that a higher-ability player has a higher probability of winning the prize than a lower-ability player. Put differently, a stronger player has an advantage over a weaker player in a contest. There are very few exceptions to this standard result. I consider a model in which being “too big” is only a necessary condition for an insolvent firm to receive a government bailout because, in addition to meeting a threshold asset size, the firm must engage in a lobbying contest in order to be bailed out. The firm has an advantage because its probability of winning the contest is increasing in its size. When the firm experiences an unfavorable price shock, I find that the balance between the size of the requisite bailout and the firm's political advantage of being “too big” determines the firm's probability of getting a bailout. Surprisingly, I find that a smaller firm may receive a bailout while a bigger firm will not, although the firm's (political) advantage is increasing in its size. This result is weakened but not overturned if the firms are uncertain about the threshold size for being considered too big. The paper's main result will not hold in a contest with independent valuations. In the bailout contest, the players have interdependent valuations.
Keywords: O10; P16; P48; 330; insolvency; bail-out; biased contests; political advantage; too-big